A Rare Cause of Unilateral Central Retinal Vein Occlusion in a Young Patient: Type III Mixed Cryoglobulinemia - Sibel Doguizi; Mehmet Ali Sekeroglu; Mustafa Alpaslan Anayol; Pelin Yilmazbas (Case Reports in Ophthalmological Medicine)
Purpose. To report a young male with unilateral central retinal vein occlusion (CRVO) associated with cryoglobulinemia. Case Presentation. A 33-year-old male without any known systemic or ocular disorder was admitted to our clinic with a complaint of visual loss for three days in his left eye. Based on the clinical, laboratory, and ophthalmological assessments, we diagnosed this case as type III mixed cryoglobulinemia with unilateral CRVO with macular edema. For treatment, two intravitreal ranibizumab injections were administered monthly and oral prednisone (64 mg/day) was begun. Subsequently, cryoglobulins became undetectable, macular edema decreased, and the visual acuity improved to 20/32 over an 8-week period. At 24 weeks, the patient’s visual acuity remained 20/32 and no recurrence was observed while the patient was still on prednisone (16 mg/day). Conclusion. Cryoglobulinemia should be considered in the differential diagnosis of the patients with CRVO.